EVALUATION OF DEVELOPMENT LEVEL OF INTEGRATED NON-COMMUNICABLE DISEASES GUIDANCE POST IN MOJOGENENG VILLAGE, JATIREJO HEALTH CENTER, MOJOKERTO REGENCY - Widarti, Luluk; Suprianto, Suprianto (Journal of Vocational Nursing, 2021)
Introduction: PTM is one of the most common causes of death in Indonesia. Based on a preliminary study of data from the Jatirejo Public Health Center in 2018, 2743 families with hypertension were found while those receiving routine treatment were 884 families. In Mojogeneng village, 163 families suffer from hypertension, but only 64 families receive regular treatment. Based on these problems, it can be said that the implementation of the PTM Posbindu in Mojogeneng Village has not run optimally, therefore it is necessary to carry out an evaluation that aims to see the level of development of the PTM Posbindu through 12 indicators according to the UKBM technical guidelines.Methods: Using a qualitative study conducted in Mojokerto Regency by involving related parties. The technique used is interview, Focus Group Discussion/FGD, observation and document review. The secondary data of the research was obtained from the results of the PTM Posbindu activities which were discussed in accordance with the research variables.Results: Variable developmental level of PTM Posbindu, Related to the implementation of activities carried out every month, 25% target obesity coverage, 35% target blood glucose, 25% target blood cholesterol, PTM counseling is carried out 3 or 4 times a year, counseling on all PTM problems, physical activity once a week 30% target, participants aged >55 years 70%, 45-55 years 55%, 35-44 years 30%, 25-35 years 15%, implementing activities 90% from the community, health financing 80% from the community , 75% independent participants, and Partnership 3 to 4 times a year.Discussion: Evaluation of the developmental level of PTM Posbindu consists of 12 indicators, the first indicator is independent category, second pratama, third middle, fourth pratama, fifth middle, sixth independent, seventh middle, eighth >55 years old and 44-55 full moon, 35-44 years old and 25-34 middle years, ninth and tenth full moons, eleventh full moons, and twelfth full moons.